North African and Colonial Troop Involvement in Southwest France, 1944–1945 - (:unkn) unknown (My University, 2013)
Based on archives conserved by the Historical Section of the French Ministry of Defence, this article examines the engagement of French North-African colonial troops in operation in southwest France in the months following the Liberation in 1944-1945. The government’s perception of this region, which had been liberated without the intervention of regular troops, resulted in giving this force more responsibility in the area of security than in military action against the German pockets on the Atlantic coastline. In assigning to this task not only colonial troops but also battalions made up of former prisoners of war who had been held captive since 1940, it provided opportunities to officers in the French Forces of the Interior, the Free French, and the former Army of Africa that had remained loyal to Vichy to make claims and basically to reinvent themselves.
Keywords: African Research